Phasic Activation of Individual Neurons in the Locus Ceruleus/Subceruleus Complex of Monkeys Reflects Rewarded Decisions to Go But Not Stop - Kalwani, Rishi M. (Society for Neuroscience, 2014)
Neurons in the brainstem nucleus locus ceruleus (LC) often exhibit phasic activation in the context of simple sensory-motor tasks. The functional role of this activation, which leads to the release of norepinephrine throughout the brain, is not yet understood in part because the conditions under which it occurs remain in question. Early studies focused on the relationship of LC phasic activation to salient sensory events, whereas more recent work has emphasized its timing relative to goal-directed behavioral responses, possibly representing the end of a sensory-motor decision process. To better understand the relationship between LC phasic activation and sensory, motor, and decision processing, we recorded spiking activity of neurons in the LC+ (LC and the adjacent, norepinephrine-containing subceruleus nucleus) of monkeys performing a countermanding task. The task required the monkeys to occasionally withhold planned, saccadic eye movements to a visual target. We found that many well isolated LC+ units responded to both the onset of the visual cue instructing the monkey to initiate the saccade and again after saccade onset, even when it was initiated erroneously in the presence of a stop signal. Many of these neurons did not respond to saccades made outside of the task context. In contrast, neither the appearance of the stop signal nor the successful withholding of the saccade elicited an LC+ response. Therefore, LC+ phasic activation encodes sensory and motor events related to decisions to execute, but not withhold, movements, implying a functional role in goal-directed actions, but not necessarily more covert forms of processing.